Pendekatan Urban Network Analysis (UNA) Untuk Mengidentifikasi Pusat Pelayanan di Kelurahan Karang Joang - Bimo Aji Widyantoro; Muhammad Fauzan Putra; Dhimas Bayu Mahardhika (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2025)
This study aims to analyze the role of Karang Joang Urban Village as a service center in Balikpapan City by applying the Urban Network Analysis (UNA) approach. Karang Joang, the largest urban village in North Balikpapan District and located in close proximity to the new capital city (IKN), is expected to undergo massive development, thus requiring the identification of optimal activity centers. The analysis employs three centrality indicators: reach, betweenness, and closeness. The results show that buildings with high reach values have the potential to become activity centers due to their good accessibility. Meanwhile, the betweenness indicator identifies buildings that serve as key connectors between areas. However, the closeness centrality values indicate that accessibility between buildings is not yet optimal, mainly due to relatively large distances between buildings and a limited road network. This study concludes that Karang Joang has the potential to function as a service center, but infrastructure improvements are required to support sustainable regional development.